Microplastic-mediated transport of PCBs? A depuration study with Daphnia magna - Gerdes, Zandra (PLoS One, 2019)
The role of microplastic (MP) as a carrier of persistent organic pollutants (POPs) to aquatic organisms has been a topic of debate. However, the reverse POP transport can occur if relative contaminant concentrations are higher in the organism than in the microplastic. We evaluated the effect of microplastic on the PCB removal in planktonic animals by exposing the cladoceran Daphnia magna with a high body burden of polychlorinated biphenyls (PCB 18, 40, 128 and 209) to a mixture of microplastic and algae; daphnids exposed to only algae served as the control. As the endpoints, we used PCB body burden, growth, fecundity and elemental composition (%C and %N) of the daphnids. In the daphnids fed with microplastic, PCB 209 was removed more efficiently, while there was no difference for any other congeners and ΣPCBs between the microplastic-exposed and control animals. Also, higher size-specific egg production in the animals carrying PCB and receiving food mixed with microplastics was observed. However, the effects of the microplastic exposure on fecundity were of low biological significance, because the PCB body burden and the microplastic exposure concentrations were greatly exceeding environmentally relevant concentrations.